2001
DOI: 10.1001/archotol.127.12.1451
|View full text |Cite
|
Sign up to set email alerts
|

Bone or Cartilage Invasion by Advanced Head and Neck Cancer

Abstract: Equivalent efficacy of treatment in the 2 groups suggests that targeted chemoradiation can be a definitive therapeutic option in patients with advanced head and neck cancer invading bony or cartilaginous structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…9,10,20 In addition, there was no difference in outcomes in patients with BCI or STI. Our findings have been corroborated by Samant et al, 12 who compared the results of concurrent intra-arterial cisplatin and radiotherapy in patients with either STI or BCI T4 disease. These findings suggest that BCI does not confer a worse prognosis than patients with STI treated with CRT.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…9,10,20 In addition, there was no difference in outcomes in patients with BCI or STI. Our findings have been corroborated by Samant et al, 12 who compared the results of concurrent intra-arterial cisplatin and radiotherapy in patients with either STI or BCI T4 disease. These findings suggest that BCI does not confer a worse prognosis than patients with STI treated with CRT.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings revealed that patients with bone invasion had similar outcomes as patients with cartilage invasion regardless of treatment approach. This has also been corroborated by the results seen by Samant et al 12 In that study, the subgroup of patients with BCI treated with CRT had no differences in overall survival. This study is limited by its small sample size.…”
Section: Discussionsupporting
confidence: 81%
“…Samant et al have provided additional support for the efficacy of CRT in patients with bone or cartilage invasion. 10 They found there were comparable survival results in 135 patients with (n ¼ 45; 2-year survival, 46.3%) or without (n ¼ 90; 2-year survival, 36.9%) bone or cartilage invasion. He concluded that organ-preservation approaches should not be withheld from patients based on presence of bone or cartilage invasion.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, it is generally thought that radiation doses that would be considered therapeutic for advanced OCC would lead to unacceptable toxicities in the form of xerostomia, or radiation-induced soft-tissue or bone necrosis. 10 These perceptions have led to OCC trials that embrace surgery as the most critical component of the multimodality schema. For example, Choi et al 11 retrospectively reviewed 861 patients with OCC treated in Korea from 1984 to 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, RTOG 9111, 10 which excluded patients with BCI, revealed improved outcomes with concurrent CRT versus radiotherapy alone or sequential CRT. In an effort to extend those outcomes to patients with BCI, Samant et al 11 revealed similar outcomes in patients with T4 locally advanced SCCHN caused by BCI or soft tissue invasion (STI) treated with CRT. Soo et al 12 reported their phase III trial evaluating those with III/IV SCCHN treated with surgery, followed by radiotherapy versus CRT.…”
mentioning
confidence: 99%